Modifikasi Pembelajaran Pendidikan Jasmani Menggunakan Kartu Ceria Dalam Meningkatkan Motivasi Berprestasi dan Konsep Diri Siswa - Djami, Jolis Joskar Anderias; Nggaa, Paulus Natalis (Universitas Persatuan Guru 1945 NTT, 2019)
The aimed of this research is to know the influence of modification of physical education learning using cheerful cards to the motivation of achievement and student self-concept at private junior high school of PGRI Kupang. This research is quasi-experiment research by wearing a model one group Pretest-postest design. Respondents numbered 60 students with research samples taken randomly; there are control groups (n = 30) and experiment groups (n = 30). The results showed that the modification of physical education learning using cheerful cards affects the motivation of achievement and self-concept of private junior high school of PGRI Kupang with a value of sig. 0.000 < 0.05.